Interstitial water geochemistry results of IODP Hole 386-M0088D - Strasser, Michael; Ikehara, Ken; Everest, Jeremy D; Maeda, Lena; Hochmuth, Katharina; Grant, Hannah; Stewart, Margaret S; Sakurai, Noriaki; Yokoyama, Takahiro; Bao, Rui; Bellanova, Piero; Brunet, Morgane; et al. (PANGAEA, 2025)
Results of interstitial water (IW) geochemistry analyses from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. Sampling for IW geochemistry took place offshore immediately upon core recovery using Rhizon samplers. A total amount of approximately 15 mL IW per sample were extracted from the core sections over a maximum rhizon retention time of 6 hours. IW main samples were subsequently split into as many as seven fractions for the following IODP standard measurements: sulfide (1.5 mL IW + 0.6 mL ZnAc 2.5%), salinity (0.5–1.5 mL), pH and alkalinity (3–4 mL), ammonium (0.5–1.5 mL), cations (3 mL IW + 0.03 mL HNO3), and anions (3 mL). In addition to IW from the core sections, samples of the bottom water (BW) were collected from the top of the trigger core using a Duran bottle and vacuum pump unit connected by tubes. For further methodological information see methods chapter in Strasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023
Keywords: International Ocean Discovery Program (IODP); IODP; Japan Trench; Porewater chemistry